The business of the business is not just the business: business sustainability as strategic element - Moçato, Elizabeth; Melo, Mary Fernanda de Sousa de; Campos, Willerson Lucas de; Polo, Edison Fernandes (Revista de Administração da UFSM, 2019)
Based on theoretical and empirical studies, better business results are possible to achieve when there is alignment between the organization’s strategy and sustainability management, as this alignment generate value for the organization and attend its stakeholders directly. Thus, this paper aims to highlight the reasons why companies should invest in sustainability, drawing up conclusions from literature and the perception of managers and coordinators of different areas in a Brazilian mining company. In order to do that, a qualitative research was conducted based on semi-structured interviews with those responsible for the mining company. As the main result, we have a synthesis of ten reasons why companies should invest in sustainability, that are: image, increase internal and external sales, valorization in the capital market, reduction of costs, improvement in company’s image before its stakeholders, reduction of risks, attraction and retention of talents, innovative capacities, competitive advantage and quick response or anticipation to legislation.